Alimentação infantil: representações sociais de mães e avós - Guerra, Adriana Queiroga Sarmento (2014)
Healthy eating in childhood is important not only for intellectual development and for growth, but in the prevention of chronic diseases in adults and pediatric patients. The study has the objective to analyze the social representations of infant feeding, built by mothers and grandmothers, Roma and non-Roma; ascertain whether or not the differentiation of social representations between mothers and Roma and non-Roma grandmothers on infant feeding and identify the influences of social representations of grandmothers on infant feeding practices. Methodology. This is an exploratory research on a qualitative approach, based on the theoretical framework of social representations. Data collection was performed using the focus group technique, corresponding of ten focus, composed of 56 subjects, groups such as mothers and grandmothers Roma and non-Roma. The data collected were processed by software Iramuteq and subsidized by the theory of social representations. Results and Comments. These research three articles presented in the results and comments were originated. Among these, the first was published; submitted for publication the second and the third was the object of defense. Through this research, it was possible to detect favorable and unfavorable points in relation to infant feeding in both groups of mothers and grandmothers Roma and non-Roma. Regarding breastfeeding Roma has the practice of exclusive breastfeeding until six months of life and keeps for a long time usually up to five to seven years. The complementary diet starts lazily with significant restrictions on infant feeding in food, according to their beliefs and myths. A positive fact is that the son of gypsy does not use a pacifier or bottle and, unlike observed in children of mothers and grandmothers non-Gypsy. The group of mothers and grandmothers did not breastfeed their children for Roma shorter period, with early introduction of other foods. Final Thoughts: In both groups, it was observed that mothers have great difficulty starting new foods, especially if they suck up more than a year to live. The intergenerational connection is very strong in Roma mothers and cultural aspects are still evident even in power.